The dynamic nexus of crop production and population growth: housing market sustainability pathway - Alola, Andrew Adewale; Alola, Uju Violet (Springer Heidelberg, 2019)
The urban poor residents in South Africa are over time known for imbalance and inadequate housing amidst recent concern of shock in food production. In studying this peculiar problem, this study investigates the cointegration and long-run equilibrium relationship of population growth, crop production, and the housing price in the country. Empirically, a quarterly data from 1975:Q1 to 2015:Q4 is employed using the conventional Autoregressive Distributed Lag. The investigation shows strong significant evidence of cointegration and a quarterly speed of adjustment of 17.2% to long run in the system. Also, as the population grows, a decline in house price index is experienced in the long run. Although unusual, adequate and sustainable housing plan, demand-supply dynamics, in respect to a country's population expansion could posit observation. But, in the short run, a strongly significant positive association is observed. It shows further that positively short-run and long-run relationships significantly exist between crop production and house price index. In reality, caution is essential in the introduction of land redistribution policy to avoid hampering the housing policies and 2030 housing target of the government.
Keywords: Housing market; Crop production; Population growth; South Africa; C22; N57; R31